Clinical and subclinical ketosis in dairy cattle. (2nd January 2019) - Manning, Al
Abstract : Much has been written about ketosis in dairy cattle, and its association with post-partum disease. This article sets out where we are now with ketosis and what the future of testing, prevention and monitoring might look like.